Zinc Removal from Wastewater by Emulsion Liquid Membrane Technique: Utilizing Response Surface Methodology to Improve Optimization and Analyze Data - Al-Shati, Ahmed Salah; Alaydamee, Hussein Hantoosh; Sultan, Abbas J.; Hasan, Zahraa W.; Kadhim, Bashar J.; Sabri, Laith S.; Majdi, Hasan Sh (Petroleum chemistry, 2025)
Metals’ potential hazards have drawn greater attention to the influence of metal pollution on water, making it a crucial subject of study in recent environmental research. This research aligns with the Sustainable Development Goals (SDGs), that aim to protect the world by addressing environmental concerns. As a consequence, understanding the impact of metal pollution on water is an essential aspect of the SDGs’ efforts to improve environmental preservation. This study provides insight into the removal of zinc ions from industrial wastewater using emulsion liquid membrane (ELM) technology. A study was conducted to investigate the use of ELM technology for removing zinc ions from industrial wastewater. Previous studies have shown that ELM can easily remove metals in their ionic form, but the presence of other organic or inorganic compounds like sulfates, phosphates, and carbonates in industrial wastewater increases their solubility and complexity of the removal. To develop the liquid membrane, a surfactant called Sorbitan monooleate (Span 80), an extractant called bis-2-ethylhexyl phosphoric acid (D2EHPA), hydrogen chloride as a reagent, and kerosene as a diluent were used. The study investigated the impact of surfactant concentration, homogenizer speed, extractant concentration, and external phase pH on zinc ion removal using a Box-Behnken design based on Response Surface Methodology (RSM). The results showed that surfactant concentration and pH had the greatest impact on removal efficiency, while homogenizer speed and surfactant extractant had a lower impact on zinc removal. The investigation adjusted numerous parameters to achieve a zinc recovery rate of more than 93% from the bioleaching solution. The most beneficial conditions were a stirring speed of 250 rpm for 10 min, 4.75% v/v Span 80, a homogenizer speed of 11 212 rpm for 8 min, a feed phase pH of 5 or 4.9, and 6% v/v D2EHPA in kerosene.